(untitled) (BIRDEM Medical Journal, 2019)
Background: Nutritional needs change throughout the various stages of life. While overall caloric needs tend to decrease with age, the requirements for individual micronutrients do not decrease. In fact, the needs for some micronutrients actually increase with age. The risk of nutritional disturbances mainly trace elements deficiencies is high during postmenopause causing or intensifying serious clinical symptoms. Methods: This cross-sectional study was carried out in the Department of Biochemistry, Mymensingh Medical College in collaboration with the Department of Obstetrics and Gynecology , Mymensingh Medical College Hospital during the period from July 2013 to June 2014. A total of 100 subjects were included in this study. Among them 50 apperantly healthy postmenopausal womenaged between 45-70 years were considered as case and another 50 regular menstruating premenopausal women aged between 30-40 years were selected as control. Results: The mean age of case and control groups was 50.5± 2.3 years and 36.5± 4.4 years respectively. In this study serum zinc levels in cases and controls were 71.54 ± 5.69 ìg /dl and 74.68 ± 5.453 ìg/dl respectively, and there was significant difference(p<0.01). Conclusion: Serum zinc level was significantly decreased in postmenopausal group in comparison to premenopausal women (p< 0.01). Estimation of serum zinc levels might be incorporated in every postmenopausal for possible prevention of complications. Birdem Med J 2019; 9(2): 147-150